Strategies to shape the international order: exit, voice and innovation versus expulsion, maintenance and absorption. Issue 2 (3rd April 2018) - Munro, Lauchlan T.
ABSTRACT: This article describes the strategies of emerging and dominant countries as they struggle over the shape of the international order. The article extends Hirschman's tripod of exit, voice and loyalty as responses to organisational decline, using Ostrom's work on social dilemmas. A country's reaction to the declining legitimacy of the post-1945 international order depends largely on whether it is a traditional OECD donor country or a developing or emerging country from the South. Developing and emerging countries are engaging in selective and partial exit, voice and innovation to change things, while dominant powers are using maintenance, absorption and expulsion to maintain their status.